(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Ceftriaxone, a third generation cephalosporin antibiotic is an important antibiotic used in the treatment of invasive infections caused by the certain bacteria such as the penicillin-resistant microorganisms like Staphyloccocus aureus, strains of S. pneumonia, S. aureus and Enterobacteriaceae , particularly among E. coli. There is increasing antimicrobial resistance of Ceftriaxone in particular against these strains of bacteria. This study has been conducted to formulate, evaluate and optimize chitosan coated ceftriaxone loaded microparticles with better efficacy and also observes the MIC against strains of bacteria. Emulsion crosslinking method was used for the formulation of microparticles of ceftriaxone by using chitosan as a polymer and glutraldehyde as a cross linking agent which is optimized by using Box-Behnken Design. Three independent variables were taken; effect of drug and the polymer ratio, effect of the stirring speed and effect of crosslinking agent and dependent variables were microparticles entrapment efficiency and the In vitro drug release. Following optimization of the formulations, physical characterization as well as entrapment efficiency and ultimately in-vitro evaluation was performed. Physical characterization include optical microscopy, SEM and DLS to check there physical properties. The method used for the formulation of microparticle had the optimum entrapment efficiency of 61.7% which was increase with the increase in the addition of the more amount of chitosan and glutraldehyde and method also achieved the good in vitro release. MIC studies of microparticles were done against Klebsiella pneumonia, Staphylococcus aureus, Streptococcus mutans, Escherichia coli and it was found that the formulations showed decrease in MIC.